2017
DOI: 10.1021/acs.inorgchem.7b01666
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Am(III)- and Pu(III)-DOTA Complexes

Abstract: The complexation of 1,4,7,10-tetrazacyclodecane-1,4,7,10-tetraacetic acid (DOTA) ligand with two trivalent actinides (Am and Pu) was investigated by UV-visible spectrophotometry, NMR spectroscopy, and extended X-ray absorption fine structure in conjunction with computational methods. The complexation process of these two cations is similar to what has been previously observed with lanthanides(III) of similar ionic radius. The complexation takes place in different steps and ends with the formation of a (1:1) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 78 publications
(89 reference statements)
3
41
0
Order By: Relevance
“…A different explanation may involve the initial formation of the [U IV (κ 4 ‐DOTA)(dmso) 4 ] complex (“out‐of‐plane”) in the synthetic solution, as shown by Kent et al . Similar coordination spheres were reported in aqueous media for DOTA complexes of Pu III ; Am III ; and Ln III , such as Ce III , Eu III , and Yb III . The separation and dissolution in aqueous solutions of the U IV out‐of‐plane complex may have led to its rapid oligomerization, as shown by Tamain et al .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A different explanation may involve the initial formation of the [U IV (κ 4 ‐DOTA)(dmso) 4 ] complex (“out‐of‐plane”) in the synthetic solution, as shown by Kent et al . Similar coordination spheres were reported in aqueous media for DOTA complexes of Pu III ; Am III ; and Ln III , such as Ce III , Eu III , and Yb III . The separation and dissolution in aqueous solutions of the U IV out‐of‐plane complex may have led to its rapid oligomerization, as shown by Tamain et al .…”
Section: Resultsmentioning
confidence: 67%
“…The absorption spectrum of the aqueous side product (Figure 2b)w as found to be similar to that reported for the [U 6 (OH) 4 (O) 4 (DOTAH) 4 ]c lusterbyT amain et al [8] The appearance of the aqueous [U 6 (OH) 4 (O) 4 (DOTAH) 4 ]o xohydroxo cluster as as ide product in aqueous solutionsc learly results from ac ompeting chemical reactiond uring the synthesis. One may argue that small traces of H 2 Oi nt he synthetic solution may have favored clusterf ormation.Ad ifferent explanation may involvet he initial formation of the [U IV (k 4 -DOTA)(dmso) 4 ]c omplex ("out-of-plane") in the synthetics olution,a s shownb yK ent et al [1] Similar coordination spheres were reported in aqueous media for DOTAc omplexes of Pu III ;A m III ; [21] and Ln III ,s uch as Ce III ,E u III ,a nd Yb III . [22] The separation and dissolution in aqueous solutionso ft he U IV out-of-planec omplex may have led to its rapid oligomerization, as shown by Ta main et al [8] for the equivalent Pu IV hexameric cluster formation from an initially formed monomerico ut-of-plane complex.…”
Section: Visible Absorption Spectroscopymentioning
confidence: 66%
“…This indicates either an important decrease in number of atoms in the first shell or a change in the coordination mode that leads to a split in the first coordination shell distances (increasing incoherency in the Eu−O distances). A split in the first coordination shell can lead to phase cancelling between EXAFS oscillations resulting in a decrease of the oscillation amplitude [44–46] . Attempts to fit the EXAFS spectrum with a unique Eu II −O distance led to unsatisfying results such as unrealistic coordination numbers (<5) and Debye–Waller factors (>0.02 Å 2 ), and ultimately poor spectral fitting.…”
Section: Resultsmentioning
confidence: 99%
“…As plit in the first coordination shell can lead to phasec ancelling betweenE XAFS oscillations resulting in a decreaseo ft he oscillation amplitude. [44][45][46] Attempts to fit the EXAFS spectrum with aunique Eu II ÀOdistance led to unsatisfy-ing results such as unrealistic coordinationn umbers( < 5) and Debye-Waller factors( > 0.02 2 ), and ultimately poor spectral fitting. An additional Os hell was then included in the fit.…”
Section: Eu II Speciationmentioning
confidence: 99%
“…“Out‐of‐cage” coordination geometry was also proved for An 4+/3+ /Ln 3+ ‐DOTA complexes [1c,2a, 13] and for an An 4+ oxo‐hydroxo cluster with supporting peripheral DOTA ligands, [1b] but it is considered as a labile step towards the specific complex, kinetically inert, “in‐cage” geometry. This “out‐of‐cage” to “in‐cage” transformation rate was shown to be inversely proportional to the solution [H + ] [14] as well, and suggested to be limited by the cyclen N‐H + groups deprotonation by solvent (H 2 O) or [OH − ] [14c,15] .…”
Section: Methodsmentioning
confidence: 94%